Efektivitas Bantuan Sosial terhadap Pemerataan Ekonomi: Studi Kasus Gerakan Circunomy - Pangayow, Laura Meirien Olivia; Lieberth, Ricard; Tanjung, Vicia Manuela; Tanjung, Vicsel Imanuel; Hermanto, Yanto Paulus (SERVIRE: Jurnal Pengabdian Kepada Masyarakat, 2025)
Socio-economic inequality remains a major challenge in Indonesia despite various social assistance programs. Many initiatives face issues of distribution and long-term dependency. At the same time, economic equity is essential for social stability and sustainable development. This study analyzes the effectiveness of the Circunomy Movement, a community-based model that integrates social assistance with local MSME empowerment through economic circulation. Circunomy involves micro-enterprise product purchases, which are redistributed as social assistance while ensuring transparency via a digital platform. Results show the participation of more than 300 MSMEs and benefits for around 1,000–1,500 individuals in Jakarta and its surroundings. The findings indicate that Circunomy is not only a mechanism of social assistance but also a tool for strengthening community-based economic equity. This bottom-up approach highlights the potential of social solidarity in achieving both social welfare and inclusive economic development.